Weight Control Related Eating Habits and Nutritional Knowledge of Male and Female College Students - Lee, Joo-Eun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: In this study, 400 college students in Cheongju were surveyed for weight control related eating habits and nutritional knowledge to provide basic data for healthy eating in adulthood. Methods/Statistical analysis: Frequency analysis was performed on general information of college students, and BMI, weight control experience, and residence were analyzed by χ2-test for distribution of men and women, and for weight control satisfaction, taste preference, eating habits, and nutritional knowledge, the mean and standard deviation were calculated and then an independent-samples t-test was conducted for both sexes Findings: The results showed that the BMI distribution of the college students was normal 54.3%, underweight 20.3%, overweight 12.0% and obese 13.4%, among which weight control experience was 68.7%. There was a significant difference in the distribution of male students in the BMI distribution as the proportion of obese was higher than female students (p<0.001), but weight control experience was more frequent in female students than male students (p<0.001). The average score of college students for weight control related nutritional knowledge was 76.50 out of 100. Among nutritional knowledge items, ‘vitamins and minerals provide calories, thus causing weight gain with excessive consumption’ showed 43.9%, and ‘skipping meals (fasting) is effective in reducing weight’ showed low response rate of 53.2%. The mean score of all students’ eating habits was 2.81 out of 5, showing a score under average (3 points). Among eating habits items showing low scores, there were ‘I eat three meals a day regularly’ with 2.32, ‘I eat breakfast regularly’ with 2.34, ‘I eat fruits every day’ with 2.56. Improvements/Applications: It is necessary establish a health-related subject as a liberal arts subject to have accurate nutritional knowledge and correct eating habits, and to provide a plan for nutrition management program.